Surgical management of a traumatic dislocation of the sternum in an English bulldog. (6th November 2014) - Serra, C. I.; Soler, C.; Moratalla, V.; Sifre, V.; Redondo, J. I.
<x xml:space="preserve">Abstract</x> A nine‐year‐old English bulldog presented with an acute history of dyspnoea, tachycardia and discomfort localising to the ventral thorax following a fall down the stairs that morning. After the dog was stabilised, thoracic radiographs revealed a luxation of the third and fourth sternebrae with dorsal displacement of the caudal segment. The sternum was reduced and stabilised with a contoured 12‐hole 3 · 5‐mm dynamic compression plate applied to the ventral surface of the sternum. The dog's initial recovery was rapid, cardiorespiratory parameters returning to normal in the first 24 hours. For 2 weeks postoperatively the dog exhibited difficulty in rising from a prone position. After this time there was a full recovery. Clinical examination at 8 months postoperatively did not reveal any abnormalities. Telephone follow‐up was performed at 18 months and no complications or cardiorespiratory compromise were reported. To the authors' knowledge, this is the first reported case of a traumatic dislocation of the sternum and its management in the dog.